2000
DOI: 10.1046/j.1365-313x.2000.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA interferes with gene function at the single-cell level in cereals

Abstract: Double-stranded RNA (dsRNA) has been shown to specifically interfere with gene function in several organisms including tobacco and the model plant Arabidopsis. Here, we report on rapid and sequence-specific interference of dsRNA with gene function in cereals. Delivery of cognate dsRNA into single epidermal cells of maize, barley or wheat by particle bombardment interfered with the function of co-bombarded UidA (GUS) and TaGLP2a:GFP reporter genes. Cognate dsRNA was also found to specifically interfere with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(41 citation statements)
references
References 33 publications
2
38
0
1
Order By: Relevance
“…However, the PE on cells transformed with pasBI-1 was not significantly different from that on controls. We obtained similar results, i.e., weak but not significant induction of resistance, by cobombardment of pGFP together with dsRNA of BI-1, which should induce sequence-specific RNA interference and thus down-regulation of BI-1 (18,22). On Ingrid, coexpression of sense or antisense BI-1 with GFP did not change the number of transformed GFP-expressing cells per shot, indicating that BI-1 Fig.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…However, the PE on cells transformed with pasBI-1 was not significantly different from that on controls. We obtained similar results, i.e., weak but not significant induction of resistance, by cobombardment of pGFP together with dsRNA of BI-1, which should induce sequence-specific RNA interference and thus down-regulation of BI-1 (18,22). On Ingrid, coexpression of sense or antisense BI-1 with GFP did not change the number of transformed GFP-expressing cells per shot, indicating that BI-1 Fig.…”
Section: Resultssupporting
confidence: 66%
“…Resulting pBI-1 and antisense pasBI-1 were sequenced to confirm that the original ORF was unchanged. To induce posttranscriptional gene silencing via RNA interference, particles were coated with dsRNA as described (18,22).…”
Section: Transient Transformation and Evaluation Of Penetration Efficmentioning
confidence: 99%
“…Although it had been established that high molecular weight dsRNAs can trigger silencing confined to bombarded cereal cells (32) and systemic silencing in C. elegans (33), it had not previously been shown that ca. 21-nt siRNAs as well as high molecular weight singlestranded RNAs of both polarities can trigger silencing able to spread from cell to cell and systemically.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that siRNAs of 21 nt in size, an intermediate of the RNA-interference pathway, are effective in suppression of gene expression in animal systems including mammals. Gene silencing induced by long dsRNA constructs has been demonstrated in transgenic plants showing resistance to virus infection (9): transient interference with endogenous gene expression (28), with virus infection in plants (29), and with reporter gene expression in plant cells (30,31). The siRNA technology offers animal virologists a new way to control viruses because the use of long dsRNA triggers the IFN response, which leads to apoptosis in most mammalian cells (32).…”
mentioning
confidence: 99%